2018
DOI: 10.21894/jopr.2017.00012
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Development of Palm Oil Mill Effluent (Pome) Final Discharge Polishing Treatments

Abstract: Raw palm oil mill effluent (POME) contains high amount of organic materials and residual oil that will impose high biological oxygen demand (BOD) and chemical oxygen demand (COD). It has a high acidic value, high total suspended solids (TSS) and is dark brownish in colour. Raw POME is a highly polluting wastewater and as such, it cannot be freely and/or directly discharged into any source of water or river without prior proper treatment. The treatment of raw POME is an important issue in palm oil mills and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Even though P. purpureum is commonly used in phytoremediation of wastewater (including POME FD), no such study regarding the effects of the POME FD on the plant's properties can be found. As POME FD contains significant amounts of nutrients (e.g., calcium, copper, magnesium, iron) and heavy metals (e.g., aluminium, arsenic, nickel), it could affect the application potential of the P. purpureum post-harvest, such as animal feed and biofuel production 16 . Therefore, in this study, P. purpureum was used as a phytoremediator to remediate POME FD and the growth performance of this grass grown on POME FD was evaluated.…”
mentioning
confidence: 99%
“…Even though P. purpureum is commonly used in phytoremediation of wastewater (including POME FD), no such study regarding the effects of the POME FD on the plant's properties can be found. As POME FD contains significant amounts of nutrients (e.g., calcium, copper, magnesium, iron) and heavy metals (e.g., aluminium, arsenic, nickel), it could affect the application potential of the P. purpureum post-harvest, such as animal feed and biofuel production 16 . Therefore, in this study, P. purpureum was used as a phytoremediator to remediate POME FD and the growth performance of this grass grown on POME FD was evaluated.…”
mentioning
confidence: 99%
“…Therefore, de-sludging is required when the sludge is more than one-third of the pond. About 85% of the palm oil mills that POME in Malaysia adopted ponding system because it is inexpensive, low capital, simple and easy to handle [14]. The palm oil industry is widely favored to the ponding system as only clay lining of ponds is needed and can be constructed easily by excavating hence low marginal cost [4].…”
Section: Conventional Methods In Pome Treatmentmentioning
confidence: 99%
“…There are incidents which reported that the digester burst and collapsed [13]. Typical configuration for ponding treatment system for POME [14]. Extended aeration is to complement the previous conventional treatment system, which shown in Figure 6.…”
Section: Conventional Methods In Pome Treatmentmentioning
confidence: 99%
“…Despite going through multiple stages of biological treatment, POME final discharge still has high colour intensity in excess of 500 ADMI (American Dye Manufacturers Index) [34]. The high colour intensity of POME is due to the high organic loading especially organic substances like lignin, tannin, humic acids and carotene which are known colour causing agents [41]. Since POME final discharge is typically channelled to open waterways, this dark brown colloidal wastewater will significantly affect the water clarity of rivers.…”
Section: Characteristics Of Pomementioning
confidence: 99%